Stone on private international law in the European Union - Stone, Peter, 1947- (Elgar European law and practice, 2018)
The harmonization of private international law in Europe has, to a very large extent, been the result of both legislation adopted at EU level and the subsequent case law arising from the interpretation of that legislation. This fourth edition of Peter Stone's authoritative work has been thoroughly revised and updated to take account of the most recent developments at both EU and national levels, including the recast Brussels I regulation on civil jurisdiction and the recast Insolvency regulation, and numerous decisions of the European and English courts. Key features include: ; comprehensive and in-depth coverage of key legislative developments within the EU in relation to private international law ; addresses key questions and identifies weaknesses in the current law, following up with suggestions for improvements ; combines perspectives from both civil law and common law traditions ; extensive tables of cases and legislation. This timely work will be an invaluable point of reference for practising lawyers, the judiciary, legislators and policy-makers throughout the EU. Academics and public officials interested in conflicts of laws will also find this a vital resource.